PRECISION DATA ACQUISITION (DAQ) MODULE WITH REMOTE REPROGRAMMING - Kochan, Roman; Kochan, Orest (International Journal of Computing, 2014)
These papers are designed precision data acquisition unit based on a 24- bit ADC type AD7712. It is designed for use in distributed information-measuring systems and networks. Flow data collection allows remote reprogramming - a replacement program of work through the serial interface during operation ( after the identification of the appropriate command ). Flow data collection to automatically perform the following procedures designed to improve the accuracy of the measurement result of : (i) the zero ; (ii) the calibration of exemplary source voltage; (iii ) correction of temperature coefficient of exemplary source voltage; (iv ) correction of quadratic integral non-linearity error of the ADC. Implementation procedures improve the accuracy of measurement error provides acceptable DC voltage ± 0.01% in working conditions and non-linearity of the transformation of not more than ±0.0003%.